How to Evaluate the Value of Human Life? - Tatyana Karabchuk; Marina Nikitina; Victoriya Remezkova; Natalya Soboleva (Journal of Economic Sociology, 2014)
The article is focused on estimation of human life value. This calculation of human life is crucial not only for practical reasons (defining amount of compensatory payments, activity of insurance companies, etc.), but also for rising the perception of social security and stability, as far as insurance is associated with minimization of risks in future. The paper describes two main approaches of how to estimate the value of human life. According to the conception of human capital, the value of life is implicitly assessed through the educational level and labour market activity. The alternative approach, “statistical value of average life”, estimates human life through the analysis of decisions when people have to evaluate their lives themselves. Furthermore, human life could be estimated indirectly, namely through economic losses of the health damage or death of employable people, amount of state compensatory payments, value of human lives given by insurance companies and so on. At the next step, the authors compare the value of human life in Russia and other countries. Human development index in Russia is relatively the same as in Romania and Kuwait. According to value of statistical life, the value of human life in Russia is very small and ranks with developing Asian countries in importance. The same low value of human life in Russia is proved by statistics on life insurance and estimation of casualties. Social and economic consequences of underestimation of human life in Russia are severe. Low value of human life in society reflects the importance of every citizen for the government and means that the state is not ready to invest much into increasing of life expectancy and quality of life.